Utilising a 1,8-naphthalimide probe for the ratiometric fluorescent visualisation of caspase-3 - Wynne, Conor; Elmes, Robert B. P. (Frontiers in Chemistry, 2024)
The development of selective and sensitive probes for monitoring caspase-3 activity–a critical enzyme involved in apoptosis–remains an area of significant interest in biomedical research. Herein, we report the synthesis and characterisation of a novel ratiometric fluorescent probe, Ac-DEVD-PABC-Naph, designed to detect caspase-3 activity. The probe utilises a 1,8-naphthalimide fluorophore covalently linked to a peptide sequence via a self-immolative p-aminobenzyl alcohol (PABA) linker. Upon enzymatic cleavage by caspase-3, the probe undergoes spontaneous degradation, releasing the free naphthalimide fluorophore, resulting in a ratiometric change in fluorescence emission. Spectroscopic studies revealed a time-dependent ratiometric fluorescent response, demonstrating the probe’s ability to visualise caspase-3 activity with high sensitivity. Enzyme kinetics such as Km (Michaelis constant), kcat (turnover number), and LOD (Limit of Detection) were obtained, suggesting that the probe possesses comparable kinetic data to other probes in literature, but with the added benefits of ratiometric detection. Selectivity studies also demonstrated the probe’s specificity for caspase-3 over other endogenous species and enzymes. Ac-DEVD-PABC-Naph may be a promising tool for the quantitative detection and fluorescent visualisation of caspase-3 activity in biological systems, with potential applications in apoptosis research and drug development.